2014
DOI: 10.1245/s10434-014-4105-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Time to Prostate-Specific Antigen (PSA) Nadir and Its Relationship to Survival Beyond Time to PSA Nadir for Prostate Cancer Patients With Bone Metastases After Primary Androgen Deprivation Therapy

Abstract: In this study, TTPN was a good prognostic indicator for PFS beyond TTPN and OS beyond TTPN in metastatic prostate cancer cases after primary ADT. Different TTPNs had different implications for predicting survival beyond TTPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 14 publications
2
37
1
Order By: Relevance
“…As the primary outcome of our study is Log(PSAVAP), only patients who developed disease progression were included for subsequent analyses. We believe that those patients who did not develop disease progression were skewed towards longer TTPN 15. While patients with longer TTPN were associated with lower Log(PSAVAP) as shown in this current study, exclusion of those nonprogressive patients might possibly underpower our study, which however still showed significant results despite such exclusion.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…As the primary outcome of our study is Log(PSAVAP), only patients who developed disease progression were included for subsequent analyses. We believe that those patients who did not develop disease progression were skewed towards longer TTPN 15. While patients with longer TTPN were associated with lower Log(PSAVAP) as shown in this current study, exclusion of those nonprogressive patients might possibly underpower our study, which however still showed significant results despite such exclusion.…”
Section: Discussionmentioning
confidence: 65%
“…We previously reported the use of survival beyond TTPN as an alternative outcome measurement in a similar cohort including patients without disease progression 15. Using survival beyond TTPN as the primary outcome, the effect of immortal time bias from TTPN on survival can be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ADT is not curative in patients with locally advanced or metastatic disease 3, 4, 5, 6, 7. Despite the initial response to ADT, most patients will experience disease progression and the development of castration-resistant PC (CRPC) 8, 9. The majority of previous studies reported that a longer time to the prostate-specific antigen (PSA) nadir was associated with better survival 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%